Differential effects of type of keyboard playing task and tempo on surface EMG amplitudes of forearm muscles - Chong, Hyun Ju; Kim, Soo Ji; Yoo, Ga Eul (Frontiers in Psychology, 2015)
Despite increasing interest in keyboard playing as a strategy for repetitive finger exercises in fine motor skill development and hand rehabilitation, comparative analysis of task-specific finger movements relevant to keyboard playing has been less extensive. This study examined whether there were differences in surface EMG activity levels of forearm muscles associated with different keyboard playing tasks. Results demonstrated higher muscle activity with sequential keyboard playing in a random pattern compared to individuated playing or sequential playing in a successive pattern. Also, the speed of finger movements was found as a factor that affect muscle activity levels, demonstrating that faster tempo elicited significantly greater muscle activity than self-paced tempo. The results inform our understanding of the type of finger movements involved in different types of keyboard playing at different tempi so as to consider the efficacy and fatigue level of keyboard playing as an intervention for amateur pianists or individuals with impaired fine motor skills.